Peranan Sains Moden Dalam Interaksi Teks Hadis: Penelitian Terhadap Hadis Berkaitan Penciptaan Janin Manusia - Mohd Yusuf Ismail; Abdul Kareem Toure (Universiti Sains Islam Malaysia, 2024)
Religio-scientific interaction towards hadith of the Prophet Muhammad has been clearly traced in the early Muslim scholar’s literatures, specifically form the third century of Hijri. Attention in the respected disciplines was significantly growing throughout the centuries as it was observed from literatures concerning to interpretation of the meaning of hadith in ‘kutub al-syūrūh’ from the fourth until tenth centuries of Hijri. However, the rapid establishment of scientific knowledge sparks stimulating conscience and argues against the result of earlier assimilation of the science and the hadith. Therefore this article addresses the issue by examining one of the most heated debate in this disciplines, which is the creation of the human foetus based on the latest scientific facts in the topic. The study employed qualitative method in which comparative analysis will be used as its main tools of investigation. In conclusion, this study argues for the need to revise the intricate interactions between the hadith and scientific exploration as some of the early understanding of Muslim scholars in the topic appear as not in accordance with the modern scientific facts. However some aspects of the hadith in this topic shows the inability of the modern science as the modern facts was foretold by the hadith more than fourteen thousands years ago.